2014
DOI: 10.4172/2329-6798.1000133
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis Characterization and Antimicrobial Activities of Azithromycin Metal Complexes

Abstract: Azithromycin is a well-established antimicrobial agent which has been widely prescribed for the treatment of respiratory tract infections owing to its high efficacy and safety. Various essential metal complexes of azithromycin were synthesized and characterized by techniques as UV, FT-IR, NMR, atomic absorption and elemental analysis. Spectroscopic studies of complexes suggested that the-N(CH 3) 2 and hydroxyl group of desosamine sugar moiety present in azithromycin has been involved in complexation i.e., azit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The oxazolidin ring of linezolid and its peptide bond may chelate with zinc/calcium. Furthermore, vancomycin [91], bacitracin [92,93], isoniazid [89], macrolides [94][95][96], ß-lactams [97][98][99][100][101][102][103][104][105][106][107], nitroxoline [108,109], and chloramphenicol [110] formed chelates or complexes with zinc and calcium, whereas streptomycin did not [89].…”
Section: Antibiotics Inhibit Metallo-matrix-proteinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxazolidin ring of linezolid and its peptide bond may chelate with zinc/calcium. Furthermore, vancomycin [91], bacitracin [92,93], isoniazid [89], macrolides [94][95][96], ß-lactams [97][98][99][100][101][102][103][104][105][106][107], nitroxoline [108,109], and chloramphenicol [110] formed chelates or complexes with zinc and calcium, whereas streptomycin did not [89].…”
Section: Antibiotics Inhibit Metallo-matrix-proteinasesmentioning
confidence: 99%
“…Mitochondrial dysfunction (S109, S110) Tetracyclines [87][88][89][311][312][313][314] Macrolides [94][95][96] Vancomycin [91] ß-lactams [97][98][99][100][101][102][103][104][105][106][107] Bacitracin [92,93] Isoniazid [89] Nitroxoline [108,109] Inhibition of MMP activity and/or reduction of gene expression in vitro Oxazolidinones (S128, S129) Tetracyclines (S111, S130-S187) Macrolides (S114-S127) Vancomycin (91, S198) ß-lactams (S111-S113) Bacitracin (S199) Isoniazid (S122, S195) Nitroxoline (S200, S201)…”
Section: S110)mentioning
confidence: 99%
“…[ 39 ] It has been demonstrated that Azi can form complexes with metal ions and be used as an efficient and safe antifungal drug. [ 40 ] Meanwhile, Azi can serve as a metal corrosion inhibitor due to its presence of heteroatoms and unsaturated bonds, forming a protective layer on metal surface. [ 41 ] Therefore, exploiting Zn ionophores as additives is expected to collectively address the mentioned challenges of Zn batteries.…”
Section: Introductionmentioning
confidence: 99%